Beyond Push and Pull: A New Theory of International Student Mobility - Liu, Wei; Lin, Xiaobing (Nordic Journal of Comparative and International Education, 2025)
The global mobility of students is a central feature of the internationalization of higher education. The discussions in the current literature on the issue of international student mobility seem to concentrate on three main questions: 1) What is the current pattern of international student mobility? 2) How do we explain the current mobility pattern? 3) More importantly, should we regard the current mobility pattern as a normal state of affairs or a cause for concern? What is missing in the current discussions is how we should steer the future direction of international mobility. Based on a review of the different theoretical approaches to understanding international student mobility, this paper aims to propose a new Glo(bal)-Noble Theory that recognizes the benefits of globalization and the role of neoliberal forces but encourages noble and mindful practices in international education to gradually narrow the gap between the rich and the poor in the world.